Molecular and Genetic Characterisation of Bacterial Cell-Cell Signalling - Bastholm, Tahlia (Curtin University, 2023)
Many bacteria use chemical signalling molecules called AHLs to communicate with other bacteria to regulate various traits, in a phenomenon called quorum sensing. AHLs are synthesised by one protein-family called LuxI, and the molecules vary between systems. This thesis describes two different quorum sensing systems in the plant associated Mesorhizobium. One uniquely requires two proteins – LuxI and a crotonase – to synthesise unusual AHLs. The second system epigenetically regulates the movement of DNA between bacterial cells.